Development of an Automotive-Relevant Recycling Process for Paper Fiber-Reinforced Polypropylene Composites - Cecile A. Grubb; Mahshid Mokhtarnejad; John Greene; John Misasi; David J. Keffer; Marton Kardos; Hendrik Mainka; David P. Harper (Recycling)
The automotive industry is under growing pressure from regulatory agencies to improve the recyclability of its plastic components. Simultaneously, manufacturers are adopting natural fiber composites in vehicles to reduce their carbon footprint and decrease reliance on petroleum-based materials. This presents a challenge at vehicle end-of-life, however, as natural fiber-reinforced polymers are substantially more difficult to recycle than their unreinforced counterparts. This study investigated the development of a mechanical recycling process for paper fiber-reinforced polypropylene composites, focusing on the impact of injection molding parameters—specifically, injection temperature and rate—on the thermal, mechanical, and water uptake properties of the composites. The results showed that processing temperature had a greater influence on composite performance than injection rate, with some limited interaction effects between the two. Higher processing intensity damaged the paper fibers, increasing the number of nucleation sites and resulting in greater polypropylene crystallinity. These structural changes reduced tensile properties at higher intensities, while flexural properties improved. Objective function analysis was applied to identify optimal processing conditions, balancing these competing trends. Overall, the findings demonstrate that paper fiber-reinforced polypropylene composites can be recycled into automotive-relevant injection molding compounds using conventional plastic manufacturing techniques, though careful tuning of processing parameters is essential to achieve optimal performance.